Maternal mycoestrogen exposure in relation to timing of birth and placental corticotropin releasing hormone concentrations in a U.S. pregnancy cohort - Alyssa Juenke; Megan C. Hansel; Carolyn W. Kinkade; Anita Brinker; Maria Bowman; Roger Smith; Richard K. Miller; Jessica Brunner; Brian Buckley; Thomas G. O’Connor; Lauren M. Aleksunes; Zorimar Rivera- Núñez; et al. (Reproductive Toxicology, 2026)

Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

Prenatal air pollution exposure and placental vasculature development among participants of the UPSIDE cohort study - Shivram Kumar; Carolyn M. Salafia; Ruchit Shah; Theresa Girardi; Richard K. Miller; Sally W. Thurston; Philip K. Hopke; David Skrill; Jessica Brunner; Donald Harrington; Yihui Ge; Yan Lin; et al. (Environmental Research, 2025)

PM2.5 and NO2 exposure during pregnancy and measures of fetal size and attained size at birth - Nafisa Nawal Islam; Sally W. Thurston; Donald Harrington; Yihui Ge; Samuel Weisenthal; Jessica Brunner; Richard K. Miller; Philip K. Hopke; Yan Lin; Emily S. Barrett; Thomas G. O’Connor; Junfeng Zhang; et al. (Air Quality, Atmosphere & Health, 2025)

Panta Rhei: a decade of progress in research on change in hydrology and society - Heidi Kreibich; Murugesu Sivapalan; Amir AghaKouchak; Nans Addor; Hafzullah Aksoy; Berit Arheimer; Karsten Arnbjerg-Nielsen; Cynthia Vail-Castro; Christophe Cudennec; Mariana Madruga de Brito; Giuliano Di Baldassarre; David C. Finger; et al. (Hydrological Sciences Journal, 2025)

Investigating the storage of organic carbon, nitrogen and phosphorus in pond sediment - Elmar M. Schmaltz; Elisabeth Peham; Hannah Forsthuber; Matthias Konzett; Thomas Brunner; David Ramler; Peter Strauss; Christian Bauer (Journal of Soils and Sediments, 2025)

Metastasis-directed stereotactic radiotherapy in patients with breast cancer: results of an international multicenter cohort study - Alexander Fabian; Daniel Buergy; Fabian Weykamp; Juliane Hörner-Rieber; Denise Bernhardt; Judit Boda-Heggemann; Montserrat Pazos; Nora Mehrhof; David Kaul; Alicia S. Bicu; Eugenia Vlaskou Badra; Susanne Rogers; et al. (Clinical & Experimental Metastasis, 2025)
Metastasis-directed therapy (MDT) for oligometastatic breast cancer (≤ 5 metastases) has shown little effect in specific scenarios of randomized trials. Therefore, we aimed to assess outcomes after metastasis-directed stereotactic radiotherapy (SRT) in various clinical scenarios. We conducted an international retrospective cohort study in thirteen centers including breast cancer patients receiving SRT to any metastatic site. Outcomes included local recurrence (LR), progression-free survival (PFS), and overall survival (OS). Cumulative incidence analysis was used for LR, Kaplan–Meier estimates for PFS and OS. Covariables included patient, disease, and SRT characteristics. We performed univariable and multivariable analyses (MVA). Among 444 patients, 751 metastases were treated with SRT. Of these, 73% were intracranial and 27% extracranial lesions. Oligometastatic disease (OMD) was present in 66% of the patients. LR after two years occurred significantly more often in intracranial (25%) versus extracranial lesions (7%). In MVA of patients with OMD treated for intracranial sites, higher performance status was significantly associated with longer PFS. Further, higher performance status, biologic subtype (HR-pos./HER2-pos.), and MDT to all sites were significantly associated with longer OS. In MVA of oligometastatic patients treated for extracranial sites, biologic subtype (HR-neg./HER2-pos.) and synchronous metastasis were associated with significantly longer PFS, whereas higher grading was associated with significantly shorter PFS. Moreover, biologic subtype (HR-neg./HER2-neg.) was associated with significantly shorter OS. In conclusion, the role of MDT for breast cancer may vary per clinical scenario. Patients with OMD treated for intracranial lesions who had MDT to all sites showed superior OS. Our results should be validated prospectively.

Increasing Hydroclimatic Whiplash Can Amplify Wildfire Risk in a Warming Climate - Daniel L. Swain; John T. Abatzoglou; Christine M. Albano; Manuela I. Brunner; Noah S. Diffenbaugh; Crystal Kolden; Andreas F. Prein; Deepti Singh; Christopher B. Skinner; Thomas W. Swetnam; Danielle Touma (Global Change Biology, 2025)

Prenatal exposure to phthalates and phthalate replacements in relation to chorionic plate surface vasculature at delivery - Emily S. Barrett; David Skrill; Elaine Zhou; Sally W. Thurston; Theresa Girardi; Jessica Brunner; Hai-Wei Liang; Richard K. Miller; Carolyn M. Salafia; Thomas G. O'Connor; Jennifer J. Adibi (Science of The Total Environment, 2025)

Socio-behavioural factors influencing meat intake and meat reduction intention in Vietnam and Switzerland - Thanh Mai Ha; Minh Hai Ngo; Mathilde Delley; Franziska Götze; Lam Thi Bui; Nhu Thinh Le; Evelyn Markoni; Anh Duc Nguyen; Bao Duong Pham; Thomas A. Brunner (Meat Science, 2024)

Factors influencing the willingness to purchase and consume microalgae-based foods: An exploratory consumer study - Bárbara Franco Lucas; Thomas A. Brunner (International Journal of Gastronomy and Food Science, 2024)

Systemic oxidative stress levels during the course of pregnancy: Associations with exposure to air pollutants - Xiangtian Wang; Yan Lin; Yihui Ge; Emily Craig; Xiaodong Liu; Richard K. Miller; Sally W. Thurston; Jessica Brunner; Emily S. Barrett; Thomas G. O'Connor; David Q. Rich; Junfeng (Jim) Zhang (Environmental Pollution, 2024)

Associations between mycoestrogen exposure and sex steroid hormone concentrations in maternal serum and cord blood in the UPSIDE pregnancy cohort - Carolyn W. Kinkade; Lauren M. Aleksunes; Anita Brinker; Brian Buckley; Jessica Brunner; Christina Wang; Richard K. Miller; Thomas G. O'Connor; Zorimar Rivera-Núñez; Emily S. Barrett (International Journal of Hygiene and Environmental Health, 2024)

Establishment of the deuterium oxide dilution method as a new possibility for determining the transendothelial water permeability - Hannes Müller; Janina Hahn; Angelina Gierke; Robert Stark; Cornelia Brunner; Thomas K. Hoffmann; Jens Greve; Oliver Wittekindt; Robin Lochbaum (Pflügers Archiv - European Journal of Physiology, 2024)
Increase in transendothelial water permeability is an essential etiological factor in a variety of diseases like edema and shock. Despite the high clinical relevance, there has been no precise method to detect transendothelial water flow until now. The deuterium oxide (D 2 O) dilution method, already established for measuring transepithelial water transport, was used to precisely determine the transendothelial water permeability. It detected appropriate transendothelial water flow induced by different hydrostatic forces. This was shown in four different endothelial cell types. The general experimental setup was verified by gravimetry and absorbance spectroscopy. Determination of transendothelial electrical resistance (TEER) and immunocytochemical staining for proteins of the cell-cell contacts were performed to ensure that no damage to the endothelium occurred because of the measurements. Furthermore, endothelial barrier function was modulated. Measurement of transendothelial water flux was verified by measuring the TEER, the apparent permeability coefficient and the electrical capacity. The barrier-promoting substances cyclic adenosine monophosphate and iloprost reduced TEER and electrical capacity and increased permeability. This was accompanied by a reduced transendothelial water flux. In contrast, the barrier-damaging substances thrombin, histamine and bradykinin reduced TEER and electrical capacity, but increased permeability. Here, an increased water flow was shown. This newly established in vitro method for direct measurement of transendothelial water permeability was verified as a highly precise technique in various assays. The use of patient-specific endothelial cells enables individualized precision medicine in the context of basic edema research, for example regarding the development of barrier-protective pharmaceuticals.

Attitudes and perceptions towards microalgae as an alternative food: A consumer segmentation in Switzerland - Bárbara Franco Lucas; Thomas A. Brunner (Algal Research, 2024)

Forestry in the Face of Global Change: Results of a Global Survey of Professionals - Austin Himes; Jürgen Bauhus; Shankar Adhikari; Saroj Kanta Barik; Hugh Brown; Andreas Brunner; Philip J. Burton; Lluís Coll; Anthony W. D’Amato; Jurij Diaci; Yonten Dorji; Ernest G. Foli; et al. (Current Forestry Reports, 2023)
Purpose of Review Forests support most global terrestrial biodiversity and contribute to the livelihood of billions of people, but these and other benefits are in jeopardy due to global change. This leads to questions, such as how to address the challenges of global change in forest management, given the lack of knowledge and deep uncertainty about future developments. In addition, many of the impediments to implement adaptation strategies are unknown. Recent Findings Here, we present an overview of results from a global survey of 754 forestry professionals (370 researchers and educators, 227 practicing foresters, 37 policymakers, 64 administrators, and 56 with other or unspecified roles) from 61 countries across 6 continents who were interested in global change issues. These professionals were asked about their opinion regarding three different adaptation strategies: resist , adapt , and transform . Most respondents agreed that the majority of global change factors will negatively influence the ability of forests to provide desired ecosystem services. Similarly, they agreed about major challenges when implementing adaptation strategies and specifically whether our current knowledge base is sufficient. These concerns were not limited to ecological aspects, but respondents also highlighted the need for a better appreciation of social/political and economic barriers, especially regarding transformation strategies. In addition, the response patterns, including differences due to economic status, highlight the importance of developing and evaluating adaptation strategies in a local social–ecological context. Summary Our study demonstrates a widespread perception on the part of forestry professionals around the world, especially among researchers and practitioners, that many global change factors will affect sustainable forest management negatively, resulting in the need for active silvicultural adaption. The results also suggest potential barriers to different adaptation strategies, particularly a relative lack of information and social acceptance for transform strategies. Further, this study highlights the importance of social and political factors and the need to understand the general public’s values regarding adaptation strategies as well as how the influence of public opinion is perceived by forest managers.

G × E interactions as a basis for toxicological uncertainty - Ilinca Suciu; David Pamies; Roberta Peruzzo; Petra H. Wirtz; Lena Smirnova; Giorgia Pallocca; Christof Hauck; Mark T. D. Cronin; Jan G. Hengstler; Thomas Brunner; Thomas Hartung; Ivano Amelio; et al. (Archives of Toxicology, 2023)
To transfer toxicological findings from model systems, e.g. animals, to humans, standardized safety factors are applied to account for intra-species and inter-species variabilities. An alternative approach would be to measure and model the actual compound-specific uncertainties. This biological concept assumes that all observed toxicities depend not only on the exposure situation (environment = E), but also on the genetic (G) background of the model (G × E). As a quantitative discipline, toxicology needs to move beyond merely qualitative G × E concepts. Research programs are required that determine the major biological variabilities affecting toxicity and categorize their relative weights and contributions. In a complementary approach, detailed case studies need to explore the role of genetic backgrounds in the adverse effects of defined chemicals. In addition, current understanding of the selection and propagation of adverse outcome pathways (AOP) in different biological environments is very limited. To improve understanding, a particular focus is required on modulatory and counter-regulatory steps. For quantitative approaches to address uncertainties, the concept of “genetic” influence needs a more precise definition. What is usually meant by this term in the context of G × E are the protein functions encoded by the genes. Besides the g ene sequence, the regulation of the gene expression and function should also be accounted for. The widened concept of past and present “ g ene expression” influences is summarized here as G e . Also, the concept of “environment” needs some re-consideration in situations where exposure timing (E t ) is pivotal: prolonged or repeated exposure to the insult (chemical, physical, life style) affects G e . This implies that it changes the model system. The interaction of G e with E t might be denoted as G e × E t . We provide here general explanations and specific examples for this concept and show how it could be applied in the context of New Approach Methodologies (NAM).

Protective role of the placental efflux transporter BCRP/ABCG2 in the relationship between prenatal cadmium exposure, placenta weight, and size at birth - Emily S. Barrett; Zorimar Rivera-Núñez; Kylie Getz; Pamela Ohman-Strickland; Ranran Zhang; Danielle Kozlosky; Cathleen L. Doherty; Brian T. Buckley; Jessica Brunner; Richard K. Miller; Thomas G. O'Connor; Lauren M. Aleksunes (Environmental Research, 2023)

Insect-based dog and cat food: A short investigative review on market, claims and consumer perception - Shahida A. Siddiqui; Thomas A. Brunner; Iwan Tamm; Paul van der Raad; Gautam Patekar; Nur Alim Bahmid; Kees Aarts; Aman Paul (Journal of Asia-Pacific Entomology, 2023)

Prenatal perfluoroalkyl substances exposure and maternal sex steroid hormones across pregnancy - Zorimar Rivera-Núñez; Carolyn W. Kinkade; Leena Khoury; Jessica Brunner; Hannah Murphy; Christina Wang; Kurunthachalam Kannan; Richard K. Miller; Thomas G. O'Connor; Emily S. Barrett (Environmental Research, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Binding of the D3-preferring antipsychotic candidate F17464 to dopamine D3 and D2 receptors: a PET study in healthy subjects with [11C]-(+)-PHNO - Mark Slifstein; Anissa Abi-Dargham; Ragy R Girgis; Raymond F Suckow; Thomas B Cooper; Chaitanya R Divgi; Pierre Sokoloff; Ludovic Leriche; Patrick Carberry; Shunichi Oya; Simon K Joseph; Marlène Guiraud; et al. (Psychopharmacology, 2020)

Artificial intelligence supported patient self-care in chronic heart failure: a paradigm shift from reactive to predictive, preventive and personalised care - Matthew Barrett; Josiane Boyne; Julia Brandts; Hans-Peter Brunner-La Rocca; Lieven De Maesschalck; Kurt De Wit; Lana Dixon; Casper Eurlings; Donna Fitzsimons; Olga Golubnitschaja; Arjan Hageman; Frank Heemskerk; et al. (EPMA Journal, 2019)
Heart failure (HF) is one of the most complex chronic disorders with high prevalence, mainly due to the ageing population and better treatment of underlying diseases. Prevalence will continue to rise and is estimated to reach 3% of the population in Western countries by 2025. It is the most important cause of hospitalisation in subjects aged 65 years or more, resulting in high costs and major social impact. The current “one-size-fits-all” approach in the treatment of HF does not result in best outcome for all patients. These facts are an imminent threat to good quality management of patients with HF. An unorthodox approach from a new vision on care is required. We propose a novel predictive, preventive and personalised medicine approach where patients are truly leading their management, supported by an easily accessible online application that takes advantage of artificial intelligence. This strategy paper describes the needs in HF care, the needed paradigm shift and the elements that are required to achieve this shift. Through the inspiring collaboration of clinical and high-tech partners from North-West Europe combining state of the art HF care, artificial intelligence, serious gaming and patient coaching, a virtual doctor is being created. The results are expected to advance and personalise self-care, where standard care tasks are performed by the patients themselves, in principle without involvement of healthcare professionals, the latter being able to focus on complex conditions. This new vision on care will significantly reduce costs per patient while improving outcomes to enable long-term sustainability of top-level HF care.

Novel concept to guide systolic heart failure medication by repeated biomarker testing—results from TIME-CHF in context of predictive, preventive, and personalized medicine - Nasser Davarzani; Sandra Sanders-van Wijk; Micha T. Maeder; Peter Rickenbacher; Evgueni Smirnov; Joël Karel; Thomas Suter; Rudolf A. de Boer; Dirk Block; Vinzent Rolny; Christian Zaugg; Matthias E. Pfisterer; et al. (EPMA Journal, 2018)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Characterization of the structure, dynamics, and productivity of mixed-species stands: review and perspectives - Miren del Río; Hans Pretzsch; Iciar Alberdi; Kamil Bielak; Felipe Bravo; Andreas Brunner; Sonia Condés; Mark J. Ducey; Teresa Fonseca; Nikolas von Lüpke; Maciej Pach; Sanja Peric; et al. (European Journal of Forest Research, 2016)

Challenges in personalised management of chronic diseases—heart failure as prominent example to advance the care process - Hans-Peter Brunner-La Rocca; Lutz Fleischhacker; Olga Golubnitschaja; Frank Heemskerk; Thomas Helms; Thom Hoedemakers; Sandra Huygen Allianses; Tiny Jaarsma; Judita Kinkorova; Jan Ramaekers; Peter Ruff; Ivana Schnur; et al. (EPMA Journal, 2015)

Vertical distribution of the soil microbiota along a successional gradient in a glacier forefield - Thomas Rime; Martin Hartmann; Ivano Brunner; Franco Widmer; Josef Zeyer; Beat Frey (Molecular Ecology, 2015)
Spatial patterns of microbial communities have been extensively surveyed in well‐developed soils, but few studies investigated the vertical distribution of micro‐organisms in newly developed soils after glacier retreat. We used 454‐pyrosequencing to assess whether bacterial and fungal community structures differed between stages of soil development ( SSD ) characterized by an increasing vegetation cover from barren (vegetation cover: 0%/age: 10 years), sparsely vegetated (13%/60 years), transient (60%/80 years) to vegetated (95%/110 years) and depths (surface, 5 and 20 cm) along the Damma glacier forefield (Switzerland). The SSD significantly influenced the bacterial and fungal communities. Based on indicator species analyses, metabolically versatile bacteria (e.g. Geobacter ) and psychrophilic yeasts (e.g. Mrakia ) characterized the barren soils. Vegetated soils with higher C, N and root biomass consisted of bacteria able to degrade complex organic compounds (e.g. Candidatus Solibacter ), lignocellulolytic Ascomycota (e.g. Geoglossum ) and ectomycorrhizal Basidiomycota (e.g. Laccaria ). Soil depth only influenced bacterial and fungal communities in barren and sparsely vegetated soils. These changes were partly due to more silt and higher soil moisture in the surface. In both soil ages, the surface was characterized by OTU s affiliated to Phormidium and Sphingobacteriales . In lower depths, however, bacterial and fungal communities differed between SSD. Lower depths of sparsely vegetated soils consisted of OTU s affiliated to Acidobacteria and Geoglossum, whereas depths of barren soils were characterized by OTU s related to Gemmatimonadetes . Overall, plant establishment drives the soil microbiota along the successional gradient but does not influence the vertical distribution of microbiota in recently deglaciated soils.

Intraguild predation in pioneer predator communities of alpine glacier forelands - Lorna Raso; Daniela Sint; Rebecca Mayer; Simon Plangg; Thomas Recheis; Silvia Brunner; Rüdiger Kaufmann; Michael Traugott (Molecular Ecology, 2014)
Pioneer communities establishing themselves in the barren terrain in front of glacier forelands consist principally of predator species such as carabid beetles and lycosid spiders. The fact that so many different predators can co‐inhabit an area with no apparent primary production was initially explained by allochthonous material deposited in these forelands. However, whether these populations can be sustained on allochthonous material alone is questionable and recent studies point towards this assumption to be flawed. Intraguild predation ( IGP ) might play an important role in these pioneer predator assemblages, especially in the very early successional stages where other prey is scarce. Here, we investigated IGP between the main predator species and their consumption of C ollembola, an important autochthonous alternative prey, within a glacier foreland in the Ö tztal ( A ustrian A lps). Multiplex PCR and stable isotope analysis were used to characterize the trophic niches in an early and late pioneer stage over 2 years. Results showed that intraguild prey was consumed by all invertebrate predators, particularly the larger carabid species. Contrary to our initial hypothesis, the DNA detection frequency of IGP prey was not significantly higher in early than in late pioneer stage, which was corroborated by the stable isotope analysis. Collembola were the most frequently detected prey in all of the predators, and the overall prey DNA detection patterns were consistent between years. Our findings show that IGP appears as a constant in these pioneer predator communities and that it remains unaffected by successional changes.

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Living on the edge: immune cells and immunopathology in the intestinal mucosa - Thomas Brunner (Seminars in Immunopathology, 2009)

Extra-adrenal glucocorticoid synthesis in the intestinal epithelium: more than a drop in the ocean? - Mario Noti; Daniel Sidler; Thomas Brunner (Seminars in Immunopathology, 2009)

850 Jahre München — 550 Jahre München in Karten - Kurt Brunner; Thomas Horst (KN - Journal of Cartography and Geographic Information, 2009)

Pharmacological manipulations of interval timing using the peak procedure in male C3H mice - Fuat Balci; Elliot A. Ludvig; Jacqueline M. Gibson; Brian D. Allen; Krystal M. Frank; Bryan J. Kapustinski; Thomas E. Fedolak; Daniela Brunner (Psychopharmacology, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Intragenic deletion in the LARGE gene causes Walker-Warburg syndrome - Jeroen van Reeuwijk; Prabhjit K. Grewal; Mustafa A. M. Salih; Daniel Beltrán-Valero de Bernabé; Jenny M. McLaughlan; Caroline B. Michielse; Ralf Herrmann; Jane E. Hewitt; Alice Steinbrecher; Mohamed Z. Seidahmed; Mohamed M. Shaheed; Abdullah Abomelha; et al. (Human Genetics, 2007)

Molecular cloning and characterization of the Fugu rubripes MEST/COPG2 imprinting cluster and chromosomal localization in Fugu and Tetraodon nigroviridis - Bodo Brunner; Frank Grützner; Marie-Laure Yaspo; Hans-Hilger Ropers; Thomas Haaf; Vera M. Kalscheuer (Chromosome Research, 2000)

Absorption and tissue distribution of various polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDDs and PCDFs) in the rat - Klaus Abraham; Thomas Wiesmller; Hermann Brunner; Ralf Krowke; Hanspaul Hagenmaier; Diether Neubert (Archives of Toxicology, 1989)

Elimination of various polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDDs and PCDFs) in rat faeces - Klaus Abraham; Thomas Wiesmller; Hermann Brunner; Ralf Krowke; Hanspaul Hagenmaier; Diether Neubert (Archives of Toxicology, 1989)

A developmental toxicity and psychotoxicity evaluation of FD and C Red Dye #3 (erythrosine) in rats - Charles V. Vorhees; Richard E. Butcher; Robert L. Brunner; Virginia Wootten; Thomas J. Sobotka (Archives of Toxicology, 1983)